Upstream : Guide. - Lasschuijt, Helga; Hessing, Marjolijn; Janssen, Nanda; Maasland, Marianne; Pijnappel, Johan; Zantkuyl, Henk; Zijlmans, Kitty; Amsterdam - Hoorn (Amsterdam - Hoorn : Stichting Upstream, 2002)
De Alwis, Tissa ; Arahmaiani ; Bade, David ; Beynon, Kate ; Bhagwati, Sandeep ; Blum, Michael ; Dick, Helmut ; Wendel, Yvonne Dröge ; Jianyi, Geng ; De Geuzen, a foundation for multi-visual research ; Gupta, Shilpa ; Haco ; Holden, Lisa ; et al.
Ihkv 400 jaar VOC, Stichting Upstream, Amsterdam- Hoorn, 07.09 t/m 20.10.2002
kunstcatalogus